2014
DOI: 10.1186/bcr3695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular effects of lapatinib in patients with HER2 positive ductal carcinoma in situ

Abstract: IntroductionHuman epidermal growth factor receptor 2 (HER2) amplification is frequent in ductal carcinoma in situ (DCIS) of the breast and is associated with poorly differentiated tumors and adverse prognosis features. This study aimed to determine the molecular effects of the HER2 inhibitor lapatinib in patients with HER2 positive DCIS.MethodsPatients with HER2 positive DCIS received 1,500 mg daily of lapatinib for four consecutive weeks prior to surgical resection. Magnetic resonance imaging (MRI) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…The proportion of HER2-positive DCIS (23.2%) was similar to that of HER2-positive invasive breast cancers (15-25%) [21,29]. Interestingly, clinical trials of anti-HER2 therapies have been initiated for HER2 DCIS [9][10][11]. The anti-HER2/neu antibody promotes cooperation between innate and adaptive immunity, warranting the use of combination therapies promoting antibody-initiated anti-tumor immune responses [37].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The proportion of HER2-positive DCIS (23.2%) was similar to that of HER2-positive invasive breast cancers (15-25%) [21,29]. Interestingly, clinical trials of anti-HER2 therapies have been initiated for HER2 DCIS [9][10][11]. The anti-HER2/neu antibody promotes cooperation between innate and adaptive immunity, warranting the use of combination therapies promoting antibody-initiated anti-tumor immune responses [37].…”
Section: Discussionmentioning
confidence: 93%
“…While the concept of surrogate subtyping for invasive cancers is well established, surrogate subtyping for DCIS has attracted much less attention, probably as a result of the lower efficacy of targeted therapeutics in DCIS compared with invasive cancers. Currently, clinical trials targeting HER2‐positive DCIS with different anti‐HER2 treatments with or without radiation are underway , and may eventually pave the way for less‐traumatic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…This has been acknowledged by recently conducted clinical trials testing the efficacy of HER2 targeting therapy with lapatinib in DCIS patients (ClinicalTrials.gov NCT00555152 and NCT00857714, respectively). The results of these trials are currently not published, however the trial results by Estevés et al assessing lapatinib in the pre-surgical setting reported significant inhibition of HER2 signalling and reduced tumor size following 4 weeks of treatment in HER2 positive DCIS patients [ 38 ]. Further, other biomarker trials have assessed the effects of trastuzumab in DCIS patients, among which, one trial has reported the results, showing no significant tumor effects in terms of proliferation and apoptosis after a single-dose monotherapy trastuzumab pre-surgically [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small prospective phase II single-arm study has also demonstrated that lapatinib (a tyrosine kinase inhibitor) interrupts the HER2/neu and epidermal growth factor receptor pathways, and significantly decreases the expressions of pHER2 and pERK1 in patients with HER2-positive DCIS. However, it did not alter the expression of Ki-67 (a proliferation marker) ( 41 ). The National Surgical Adjuvant Breast Project B-43 trial is a large phase III RCT (target recruitment: 2,000 patients) that is evaluating the addition of trastuzumab to standard treatment using surgery and RT (NCT00769379) ( 42 ).…”
Section: Role Of Systematic Therapy For Dcismentioning
confidence: 99%